Review Paper on Tuned Mass Damper: Investigating the Effectiveness of Tuned Mass Dampers for Vibration Control in Structures (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Now a days, structures are continuously increasing in the construction industries which are having a very low damping value. The structures can easily fail under structural vibrations induced by earthquake and wind, some several techniques are available today to control the vibration of the structure, TMD is one of these techniques are use today. Some investigations are carried out to identify the importance and performance of tuned mass damper in different structures. In this thesis, a one-storey and a two-storey building frame models are developed for shake table experiment under sinusoidal excitation to observe the response of the structure with and without TMD. The TMD is tuned t o the structural frequency of the structure keeping the stiffness and damping constant. Various parameters such as frequency ratio, mass ratio, tuning ratio etc. are considered to observe the effectiveness and robustness of the TMD in terms of percentage reduction in amplitude of the structure. Then the responses obtained are validated numerically using finite element method. From the study it is observed that, TMD can be effectively used for vibration control of structures.